Conversations with Classic Film Stars : Interviews from Hollywood's Golden Era - Miller, Ron, 1939-; Miller, Ron, 1939-; Bawden, James; Bawden, James (Book collections on Project MUSE., 2016)
Bawden and Miller present an astonishing collection of rare interviews with the greatest celebrities of Hollywood's golden age. Conducted over the course of more than fifty years, they recount intimate conversations with some of the most famous leading men and women of the era. Each interview takes readers behind the scenes with some of cinema's most iconic stars, as the actors convey unforgettable stories.